2022
DOI: 10.1177/02537176221096769
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Challenges and Reasons for Not Availing Rehabilitation Services Among Families of Adolescents with Autism Spectrum Disorder: A Qualitative Study

Abstract: Background: Autism spectrum disorder (ASD) is a lifelong condition requiring continued rehabilitation services. However, children with ASD who seek rehabilitation services tend to drop out once they enter puberty, because of varying reasons, some of which are unknown. This study intended to explore the reasons for not availing of rehabilitation services in families of adolescents with ASD and the parental challenges in taking care of adolescents with ASD. Method: The study followed a descriptive qualitative re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“… 15 A recent qualitative study cited financial difficulties and nonimprovement as the reasons for discontinuing rehabilitation services for adolescents with autism. 16 The same barriers can exist for the AwASD. The lack of affordable long-term residential services is an established problem India and other LAMICs face.…”
Section: Discussionmentioning
confidence: 79%
“… 15 A recent qualitative study cited financial difficulties and nonimprovement as the reasons for discontinuing rehabilitation services for adolescents with autism. 16 The same barriers can exist for the AwASD. The lack of affordable long-term residential services is an established problem India and other LAMICs face.…”
Section: Discussionmentioning
confidence: 79%
“…High SLS session costs were one of the most reported reasons to discontinue receiving the services, consistent with the literature investigating financial constraints as barriers to accessing different rehabilitation services. [51][52][53] This financial concern is valid, as the average monthly cost of therapy sessions is reported to be between a quarter and a third of a family's total monthly income in Jordan. 14 A study conducted in the US found that the overall cost of raising a child with ASD across his/her lifespan is over USD1 million.…”
Section: Factors Associated With Parents' Levels Of Satisfaction With...mentioning
confidence: 99%